An ultra-low-cost and adjustable in-house electrospinning machine to produce PVA nanofiber - Ika Dewi Wijayanti; Ari Kurniawan Saputra; Faris Ibrahim; Amaliya Rasyida; Putu Suwarta; Indra Sidharta (HardwareX, 2022)
Electrospinning is a method that uses a high-voltage electric field to fabricate nanofiber by charging and ejecting a polymer solution through a syringe. Compared to other methods, it produces nanofiber using simple and easy techniques. The widespread usage of the commercial electrospinning machines (Spinboxsystems)-BASIC KIT type for beginners is limited due to its price of over USD15,595. Additionally, the Original Equipment Manufacturer (OEM) spare parts are expensive to replace, which increases the production cost of Polyvinyl Alcohol (PVA) polymer nanofiber and hinders its application in various fields. This led to the successful design and development of an in-house built electrospinning machine at a total cost below USD2,000. The new machine is easy and simple to operate while also producing PVA nanofiber with excellent properties.